Investigating Bilingual Processing: The Neglected Role of Language Processing Contexts - Wu, Yan Jing; Thierry, Guillaume (Frontiers in Psychology, 2010)
How do the two languages of bilingual individuals interact in everyday communication? Numerous behavioural and event-related brain potential studies have suggested that information from the non-target language is spontaneously accessed when bilinguals read, listen, or speak in a given language. While this finding is consistent with predictions of current models of bilingual processing, most paradigms used so far have mixed the two languages by using language ambiguous stimuli (e.g., cognates or interlingual homographs) or explicitly engaging the two languages because of experimental task requirements (e.g., word translation or language selection). These paradigms will have yielded different language processing contexts, the effect of which has seldom been taken into consideration. We propose that future studies should test the effect of language context on cross-language interactions in a systematic way, by controlling and manipulating the extent to which the experiment implicitly or explicitly prompts activation of the two languages.